Student & tutor consensus: a partnership in assessment for learning. Issue 6 (18th August 2017) - Thompson, James; Houston, Don; Dansie, Kathryn; Rayner, Timothy; Pointon, Timothy; Pope, Simon; Cayetano, Anthea; Mitchell, Brad; Grantham, Hugh
Abstract: The mistakes made when attempting tasks often prove to be some of the most invaluable learning experiences. Despite this, outcome and results driven assessment formats largely penalise student performance errors or reward students who succeed by chance. The consequences of this paradigm are visible effects on student relationships with assessment. The student–tutor consensus approach to assessment was introduced to capture student learning achieved 'from' assessment to complement the measurement of performance outcomes. This approach parallels student and tutor judgement in a grade negotiation, affording the student an opportunity to share with their assessor what they have learned from the assessment activity. This student self-awareness was then considered alongside the conventional outcome-based score awarded by the tutor to generate a final grade for the assessed activity. Our study evaluated the perceptions of 90 undergraduate students enrolled in the bachelor of paramedic studies, who participated in this novel assessment approach as part of a final-year capstone topic. The results comprehensively indicated value for all aspects of the assessment approach, as well as a recognition that the skills will be useful in their future professional roles.